2011
DOI: 10.1530/eje-10-0930
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of 5α-reductase-2 deficiency in an adult female 46XY DSD clinic

Abstract: Context: The late presentation of steroid 5a-reductase-2 (SRD5A2) deficiency in females is poorly characterised. The ratios of 5a/5b-reduced metabolites of adrenal steroids in a urine steroid profile (USP) can give an indication of SRD5A2 deficiency, although the diagnostic cut-off for 5a/5b ratios are not clearly defined in genetically confirmed cases. Objective: The aim of this study was to establish the frequency of SRD5A2 deficiency in an adult clinic for disorders of sexual development (DSD) focussing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 34 publications
5
43
0
1
Order By: Relevance
“…In these circumstances, genetic testing is required. In a previous study, we found that SRD5A2 mutations occurred in 43% of women in this clinical subgroup (14). We now extend this work by presenting the results of screening for HSD17B3 and AR mutations in partially virilised women with 46,XY DSD of unknown aetiology.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In these circumstances, genetic testing is required. In a previous study, we found that SRD5A2 mutations occurred in 43% of women in this clinical subgroup (14). We now extend this work by presenting the results of screening for HSD17B3 and AR mutations in partially virilised women with 46,XY DSD of unknown aetiology.…”
Section: Introductionsupporting
confidence: 59%
“…Prader staging at birth was estimated from available information and cannot be considered perfectly accurate, but is included to convey an idea of virilisation at birth. All subjects had urinary steroid profiles performed to exclude SRD5A2 deficiency as described previously (14).…”
Section: Subjectsmentioning
confidence: 99%
“…Eleven articles mentioned the methodology of their DHT assays. USP was used for diagnosing 5ARD in 3 studies, with all the patients showing low 5␣-and 5␤-reduced steroid metabolite ratios (5,10,12 ). Regarding molecular diagnosis, 141 patients (94.6%) had 2 mutations detected in SRD5A2 to confirm the diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic guidance for disorders in sexual development is based almost entirely on pediatric experience, whereas very few guidelines are available for adults [10]. These genetic disorders have a variety of causes, such as SRY gene mutations, resulting in cases of pure gonadal dysgenesis [11], steroidogenic factor mutations (NR5A1) and mutations of the genes encoding the androgen receptor, such as 17β-hydroxysteroid dehydrogenase-3 and 5α-reductase-2, which form a poorly defined clinical group known as partial androgen insensitivity syndrome (PAIS) [5,7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…These genetic disorders have a variety of causes, such as SRY gene mutations, resulting in cases of pure gonadal dysgenesis [11], steroidogenic factor mutations (NR5A1) and mutations of the genes encoding the androgen receptor, such as 17β-hydroxysteroid dehydrogenase-3 and 5α-reductase-2, which form a poorly defined clinical group known as partial androgen insensitivity syndrome (PAIS) [5,7,9,10]. Morris syndrome or testicular feminization is the most common form of PAIS [4], and is the form that we strongly believe our patient presented with.…”
Section: Discussionmentioning
confidence: 99%